Aplicabilidade de imagens obtidas a partir de aerofotogrametria realizada com aeronave remotamente pilotada como subsídio à gestão ambiental - Avila, Calinca Barão de (2019)
The increasing use of natural resources, considering the significant impacts on the environment that may result from this use, implies the need for carrying out studies, especially using new technologies to understand these impacts broadly, thus supporting the environmental management and indicating alternatives to minimize adverse environmental effects. The justification for developing this doctoral dissertation is based on these environmental issues and it focuses on the use of remote sensing technology as a tool for the generation of aerial images with high level of detail from the use of Remotely Piloted Aircraft (RPA). The purpose of this study was to evaluate the applicability of the information obtained from RPA images for the elaboration of environmental diagnosis as a support to the improvement of the environmental management, considering the technical issues of the flight. Two sample areas with different characteristics (vegetation and water physiognomy, and variation in ground slope) were selected. The flights were carried out in both areas at heights of 50 m, 80 m and 110 m in relation to the ground level at a reference point; ground control points were used in both areas. In the next step of the flight execution, the Agisoft Photoscan software was used to process the images and to obtain the products, orthophotomosaic and Digital Elevation Model - DEM. After that, statistical analyzes of the data from the products were carried out to evaluate the accuracy in situations of using or not the ground control points, and the classification of the products according to the Brazilian Cartographic Accuracy Standard of Digital Cartographic Products (PEC-PCD), by the use of GeoPEC software. It was also verified the accuracy of flight heights regarding the classification of ground covering physiognomies using the Support Vector Machine algorithm in R programming language. The results obtained in this study converge to the need of using ground control points to obtain more accurate products, when necessary. In addition, according to the assessments of the planialtimetric positional accuracy of the products for the different flight heights, it is suggested that the flights should be executed at 80 m and 110 m. Regarding the results of physiognomy classification, flight heights of 80 m and 110 m did not differ statistically. In this context, considering other technicaleconomic aspects (coverage area, flight autonomy, data processing time in the software), it is possible to indicate that the flight at 110 m has better efficiency for the generation of orthophotomosaic as a support for environmental management.